Metal(loid) distribution and Pb isotopic signatures in the urban environment of Athens, Greece - Kelepertzis, Efstratios; Komárek, Michael; Argyraki, Ariadne; Šillerová, Hana (Environmental pollution (1987), 2016)
Lead concentrations and isotopic compositions of contaminated urban soils and house dusts from Athens, Greece, have been determined to identify possible sources of Pb contamination and examine relationships between these two environmental media. Different soil particle sizes (<2000 μm, <200 μm, <100 μm, <70 μm, <32 μm) and chemical fractions (total, EDTA-extractable and acetic acid-extractable (HAc)) were analyzed for their Pb content and isotopic composition. Metal(loid)s (Pb, Zn, Cu, As, Ni, Cr, Mn, Fe) are significantly enriched in the finest fraction. The Pb isotopic compositions were similar for the different soil particle size fractions and different chemical extractions. The HAc extraction proved to be a useful procedure for tracing anthropogenic Pb in urban soil. The range of (206)Pb/(207)Pb ratios (1.140-1.180) in Athens soil suggests that the Pb content represents an accumulated mixture of Pb deposited from past vehicular emissions and local natural sources. The contribution of anthropogenic Pb to total soil Pb ranged from 36% to 95%. The Pb isotopic composition of vacuum house dusts ((206)Pb/(207)Pb = 1.1.38-1.167) from Athens residents is mostly comparable to that of urban soil suggesting that exterior soil particles are transferred into homes. As a result, anthropogenic Pb in house dust from Athens urban environment principally originated from soil particles containing Pb from automobile emissions (former use of leaded gasoline).
Keywords: monitorování životního prostředí; látky znečišťující půdu; Trace Elements; olovo; Environmental Monitoring; prach; Vehicle Emissions; Řecko; Lead; půda; znečištění životního prostředí; velikost částic; Soil Pollutants; Environmental Pollution; výfukové emise vozidel; Greece; stopové prvky; Soil; Particle Size; Dust